Responses of two contrasting saline‐alkaline grassland communities to nitrogen addition during early secondary succession. (2nd March 2015) - Bai, Zhenjian; Gao, Ying; Xing, Fu; Sun, Shengnan; Jiao, Deyu; Wei, Xiuhong; Mu, Chunsheng; Michalet, Richard
Abstract Question (1) How do secondary successional dynamics differ in high and low saline‐alkaline grassland communities in semi‐arid lands; and (2) does nitrogen (N) enrichment promote plant secondary succession towards a perennial community under saline‐alkaline stress? Location Saline‐alkaline grassland in northeast China. Methods We selected two early successional communities differing in soil saline‐alkaline stress and floristic composition: one 'high‐stress community' co‐dominated by the annual grass Chloris virgata and the annual forbs Artemisia scoparia and Kochia sieversiana, and one 'low‐stress community' dominated by the annual forb K. sieversiana. A complete randomized design experiment with five N addition levels was conducted in triplicate for four consecutive years (2008–2011). The vegetation variables (above‐ground biomass of individual species, functional group, community level, community species richness) and soil characteristics (pH, electrical conductivity as a proxy for salinity) were investigated every year. Detrended correspondence analysis (DCA) was used to evaluate the successional trajectories. Results DCA revealed clear differences in species composition and successional trajectories between the two communities. There were few changes in the species composition of the high‐stress community, with annual species dominating all the plots over the 4 yr. However, most of the low‐stress communities developed from the annual‐dominated stage to the perennial‐dominated stage. N addition had no effect on the relative biomass of the perennial functional group in the two communities. Thus, N addition did not obviously promote plant succession towards a perennial community, even under low saline‐alkaline stress. Species richness did not respond to N addition in the high‐stress community, whereas species richness declined across the N addition gradient in the low‐stress community. Conclusion Our results provided direct empirical evidence that high saline‐alkaline stress limits plant community succession, and low saline‐alkaline stress communities exhibit a succession direction from the annual‐dominated stage to the perennial‐dominated stage. Interestingly, replicates within the same treatment under low‐stress conditions did not develop towards a similar community composition, indicating the importance of environment heterogeneity at a small spatial scale. N addition did not promote the expected perennial plant succession; however, N enrichment reduced plant diversity and enhanced above‐ground biomass, suggesting that artificial N addition (e.g. N deposition) may have an important effect in our system.